Responses to persuasive messages encouraging professional help seeking for depression: comparison between individuals with and without psychological distress - Machi Suka; Takashi Yamauchi; Hiroyuki Yanagisawa (Komiyama Printing Co. Ltd, 2019)
Abstract Background The persuasive effect of health messages can depend on message features, audience characteristics, and target behaviors. The objective of this study was to compare the responses to persuasive messages encouraging professional help seeking for depression between individuals with and without psychological distress. Methods A cross-sectional web-based survey was conducted on Japanese adults aged 35-45 years, who randomly received one of three persuasive messages that aimed to promote help-seeking intentions for depression. The primary message statements were as follows: (1) depression can happen to anyone, (2) depression needs treatment, and (3) depression improves with treatment. Participants rated the messages in terms of comprehensibility, persuasiveness, emotional response, and intended future use. Help-seeking intention for depression was measured using vignette methodology before and after exposure to the messages. Eligible participants who had not received medical treatment for their mental disorders were classified as either distressed (K6 score ≥ 5, N = 824) or non-distressed (K6 score < 5, N = 1133) and analyzed. Results No significant differences in comprehensibility or persuasiveness scores were observed between the messages, but the distressed group had significantly lower scores than the non-distressed group. Negative emotional responses such as surprise, anger, fear, sadness, guilt, and anxiety were significantly stronger when reading message 2, while a positive emotional response such as happiness was significantly stronger when reading message 3. These emotional responses were more prominent in the distressed than in the non-distressed group. After reading messages 1, 2, and 3, the proportions of participants in the distressed group who reported having a positive help-seeking intention increased by 35.1%, 32.1%, and 27.7%, respectively, and by 6.4%, 17.3%, and 15.2%, respectively in the non-distressed group. Multiple logistic regression analysis among participants having no help-seeking intention before exposure to the messages showed that message 2 had a significantly greater effect of increasing help-seeking intentions in the non-distressed group. Conclusion The exposure to persuasive messages may promote help-seeking intentions for depression. It seems likely that loss framing will work better than neutral and gain framing. Meanwhile, the responses to persuasive messages may differ to some extent between distressed and non-distressed individuals, as individuals with psychological distress are likely to be more susceptible to persuasive messages than those without. Trial registration Not applicable; this is not a report of intervention trial.